Antifungal and aflatoxin B1 inhibitory efficacy of nanoencapsulated Pelargonium graveolens L. essential oil and its mode of action. (August 2020) - Kujur, Anupam; Kumar, Akshay; Yadav, Amrita; Prakash, Bhanu
Abstract: The study reports the antifungal and aflatoxin B1 (AFB1 ) inhibitory mode of action of nanoencapsulated Pelargonium graveolens L. essential oil (Ne-PGEO). Nanoencapsulation of PGEO was prepared using chitosan nanoparticles and interactions were confirmed by scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) analysis. Chemical composition of PGEO was explored by gas chromatography-mass spectrometry (GC-MS) analysis where citronellyl formate (19.2%), linalool (15.2%), menthone (16.7%), and isomenthone (12.2%) were identified as the major compounds. Ne-PGEO inhibited the growth and aflatoxin B1 production by Aspergillus flavus at 1.00 μLmL −1, which was lower than the free PGEO at 1.25 μLmL −1 . The antifungal and aflatoxin B1 inhibitory mechanism of Ne-BPEO were related to a decrease in ergosterol content, carbon source utilization, enhancement of ions leakage, and impairment in the functioning of the ver-1 gene. In addition, the Ne-PGEO effectively preserves the organoleptic (color, taste, odour, and texture) and nutritional properties of the model food (maize grain). In view of enhanced antifungal, anti-aflatoxin activity, and sensory attributes, the results suggested that Ne-PGEO could be used as a plant-based food preservative to enhance the shelf-life of food commodities. Highlights: Chemical characterization of Pelargonium graveolens essential oil (PGEO). Nanoencapsulation of PGEO using chitosan of low molecular weight (LMWC). Antifungal and aflatoxin B1 inhibitory activity of nanoencapsulated PGEO. Elucidation of the antifungal mode of action. Recommended LMWC as an encapsulating material for essential oils.